Predictors of heart failure in children with congenital heart disease - Meily Elven Nora; Indah Kartika Murni; Sasmito Nugroho; Noormanto Noormanto (Paediatrica Indonesiana, 2022)
Background Heart failure continues to be a significant contributor to morbidity and mortality in children with congenital heart disease (CHD). Little is known about heart failure in children. Identifying predictors of heart failure in children with CHD can serve to guide preventive strategies to heart failure. Objective To understand the predictors of heart failure of children with congenital heart disease. Methods A nested, case-control study was performed using secondary data based on a prospective study previously conducted in Dr Sardjito Tertiary Hospital in Yogyakarta in years 2011-2013. We included children aged 1 month-18 years who had been diagnosed with CHD by echocardiography. Age, sex, type of CHD, CHD complexity, as well as presence of syndrome, no pulmonary obstruction, pneumonia, and malnutrition were analyzed as potential predictors of heart failure. Results are presented as odds ratios (OR) with 95% confidence intervals (95%CI). Results A total of 2,646 children were hospitalized in Dr Sardjito Tertiary Hospital during the study period. Congenital heart disease was noted in 216 children (8.16%), 200 (7.5%) of whom met the inclusion criteria. The 100 children with heart failure had median age of 1.5 years and 15% died during hospitalization. Multivariate analysis revealed that acyanotic CHD (OR 2.69; 95%CI 1.45 to 5.00), no pulmonary obstruction (OR 3.05; 95%CI 1.33 to 6.99) and the presence of pneumonia (OR 2.04; 95%CI 1.03 to 4.06) were statistically significant as independent predictors of heart failure in children with CHD. However, sex, age, CHD complexity, as well as presence of a syndrome, and malnutrition were not significantly associated with heart failure in children with CHD. Conclusion The predictors of heart failure in children with CHD were acyanotic CHD, no pulmonary obstruction, and presence of pneumonia.